Antiviral Activity of Rosa damascena Mill. and Rosa alba L. Essential Oils against the Multiplication of Herpes Simplex Virus Type 1 Strains Sensitive and Resistant to Acyclovir - Neli Vilhelmova-Ilieva; Ana Dobreva; Rositsa Doynovska; Dimo Krastev; Milka Mileva (Biology, 2021)
Background: The specific chemotherapeutics against herpes simplex virus type 1 (HSV) are nucleoside analogues such as acyclovir (ACV), but the most important problem is the formation of resistant mutants. The search for new therapeutic alternatives leads us to the purpose of investigating the effects of Rosa damascena Mill. and Rosa alba L. essential oils on the viral reproduction of susceptible (Victoria) and acyclovir-resistant (R-100) strains of HSV-1 replication in vitro, individually and in combination with acyclovir. Methods: Cytopathic effect inhibition test was used for assessment of antiviral activity of the oils, and the three-dimensional model of Prichard and Shipman was applied to evaluate the combined effect of oils with ACV on HSV-1 replication. Results: Both oils do not affect the replication of viral strains; they are able to influence only viral adsorption and extracellular virions and protect healthy cells from subsequent infection. In combination with lower doses of acyclovir, both oils demonstrate a significant synergistic effect on the replication of HSV-1, which is more contagious than the Victoria strain. Conclusions: The nonspecific mechanism of the reduction in viral reproduction caused by rose oils and the synergistic effect of their co-administration with the lower doses of specific inhibitor ACV makes them suitable therapeutics for overcoming viral resistance to HSV-1 infections.